The Influence Of Learning Styles On Students' Learning Outcomes In Class IX In Indonesian Language Subjects At SMP YB Prabumulih - Syelly Eka Permatasari; Syella Nurchaliza (Jurnal Multidisiplin Sahombu, 2025)
This research aims to determine the learning styles of class IX students at SMP YB Prabumulih in Indonesian language subjects as well as determine the learning outcomes of class IX students and to determine the influence of learning styles on learning outcomes in Indonesian language subjects. This research uses a quantitative descriptive approach using the correlation method. The subjects of this research were class IX students with a total of 30 students. The instruments used were learning style questionnaires and documentation. The research data collected was analyzed using quantitative descriptive analysis techniques with percentages, product moment correlation and simple regression analysis. The results of research regarding the influence of learning styles on the learning outcomes of class IX students in Indonesian language subjects are as follows: (1) The learning style of class IX students is predominantly visual learning style with a percentage of 50% with a total frequency of 15 out of 30 respondents, while the auditory and kinesthetic learning styles respectively are 26.6% with a total of 8 students and 23.3% with a total of 7 students. (2) There is no significant influence of learning style on the learning outcomes of class IX students in Indonesian language subjects. The implication of this research is that this research provides information for educators to apply learning methods that can accommodate students' learning methods, so that students are more active in participating in the learning process.